Comparative Analysis of T. Aman Rice Cultivation under Different Management Practice in Coastal Area - Razzaque, MA; Rafiquzzaman, S (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The field experiment was carried out at Multilocation testing site Barguna in kharif -II seasons of 1999 and 2000 to find out the probable reason of yield gap of T. aman rice (BR-23) between demonstration plot (DP) with Research management and Non-demonstration plot (NDP) with Farmer management practices. Across the years there exists a big gap in yield (1220 kg ha-1) between DP and NDP. DP gave about 25.15% higher yield than NDP due to use of best quality seed, appropriate age of seedlings (30 days), closer spacing, optimum number of seedlings per hill, use of balanced fertilizer and pest control in proper time. Although cultivation cost of DP was higher (Tk.2218 ha-1) than that of NDP. Demonstration plots showed higher benefit cost ratio (2.28) than non-demonstration plot (1.98). Key words: Coastal area, T. aman rice, farmer practice, research management, yield gap. DOI = 10.3329/jard.v5i1.1460 J Agric Rural Dev 5(1&2), 64-69, June 2007